Mártires de abril: o MST semeando a utopia camponesa - ABE, Marlene Naoyo (2004)
The description of the Mártires de Abril Nesting of and the analysis of the processes of construction of practical and the speech on the is organization anda management are the object of this work. In this way it is that if it defined as thematic the Study of the Forms of Organization of Nesting of the MST with the perspective to think the social processes that is had been constructing in the nestings of the Agrarian Reformation of the MST in Pará, and its complexity, from the experience of the Mártires de Abril Nesting that presents peculiarities. The form of organization of the production is an attempt of if to implant the project of organization of nesting of the MST that, in this works, thus had been called: Collective group or Production in the System of Cooperation; Half-collective or Familiar Production Integrated and Individual or Not Integrated Familiar Production. That perspective defined as objective do work: to understand the limits and the possibilities of implementation of the forms of organization of nesting of the MST, being associated collectivism and familiar management, from the experience of the Mártires de Abril Nesting; to identify to the limits and the possibilities of the forms of organization of the collective production in a perspective of construction of the nesting proposal; to identify to the social representations in the process of construction of the social, economic organization and politics of the nesting. It was possible to identify that in the Mártires de Abril Nesting it predominates the perspective form of organization of the collective production with possibility of if developing the half-collective one and the individual one; existence of differentiation in the politician-ideological level of each seated person, resulting in the distinction of the periods of traing of development of the base nuclei, what it goes to determine the form of organization of each nucleus and the reproduction strategies and that the context that the Mártires de Abril Nesting presents is of period of training in development, with expression of still evidences conflicts, face to the process of definition of a proper form of nesting organization. However, a trend exists, in average stated period, to the configuration of a definite project as a new alternative of nesting with cultural elements of the old form of production, mixed to the new one proposal based in the half-collective exploration and diversified cultures.